KELAYAKAN USAHA NELAYAN JARING INSANG DI PULAU KOSONG KOTA JAYAPURA - Tuhumena, Lolita Constantia; Warpur, Maklon; Rumahorbo, Basa T; Ayer, Popi Ida Laila; Titalessy, Pisi Bethania; . Risakotta, Tesalonika K (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
Productive fishing gear for catch small pelagic fish and demersal is set gillnet that use by fisherman in empty island. Effort that wrestled with this need to know the income for development, because great income wii not give profit and welfare to fisherman or ship owner in Empty Island, if capital and out cost greater than income. For that purpose researched are describe net capture equipment, analyze income and analyze feasibility of gillnet fisherman in society. The study was conducted for 6 months from June till November 2023 with use primary and secondary data, then used analyze income and investment criteria. Based on the results for research that fisherman of gillnet in empty island is Rp 207.246.667,-/year. Investment criteria obtained value NPV>1,(475.200.000-),IRR> discount rate(11%) dan Net B/C ratio >1 (4.980,-) indicating that fisherman of gillnet in empty island is a well run.